The Effect of Point Illustration Explanation (PIE) Strategy Towards Students' Descriptive Writing at the Tenth Grade Students of SMAN 1 Malingping, Lebak-Banten in Academic Year 2023/2024 - Aminah, Siti; Sudirman, Ade; Gumelar, Rizdki Elang (Journal of Contemporary Issues in Primary Education, 2024)
This study aims to evaluate the Effect of the Point Illustration Explanation (PIE) Strategy on Students' Writing Skills in Descriptive Texts at the Tenth Grade of SMAN 1 Malingping, Lebak-Banten, in the 2023/2024 academic year. The PIE strategy involves using concrete examples, in-depth explanations, and clear illustrations to help students understand and develop their descriptive writing skills. This quantitative study employs a quasi-experimental method with a sample of 74 tenth-grade students divided into an experimental class (using the PIE strategy) and a control class (using the KWL strategy). Data were collected through pre-tests and post-tests, and analysed using normality tests, homogeneity tests, and paired t-tests with SPSS 22. The results indicate a significant effect of the PIE strategy on students' descriptive writing skills, as evidenced by a t-value of -28.066 with df 74 and a two-tailed significance of 0.000, meaning Ha is accepted and Ho is rejected. In conclusion, the PIE strategy significantly improves the descriptive writing skills of tenth-grade students at SMAN 1 Malingping, enhancing their understanding of descriptive writing structures and techniques, increasing motivation, helping them develop ideas more thoroughly, and improving their ability to present clear and creative descriptions.